The Effect of the Stretch-Shortening Cycle in the Force–Velocity Relationship and Its Association With Physical Function in Older Adults With COPD - Navarro-Cruz, Roberto; Alcazar, Julian; Rodriguez-Lopez, Carlos; Losa-Reyna, Jose; Alfaro-Acha, Ana; Ara, Ignacio; García-García, Francisco J.; Alegre, Luis M. (Frontiers in Physiology, 2019)
This study aimed to evaluate the effect of the stretch-shortening cycle (SSC) on different portions of the force-velocity (F-V) relationship in older adults with and without chronic obstructive pulmonary disease (COPD), and to assess its association with physical function. The participants were 26 older adults with COPD (79±7 years old; FEV1 = 53±36% of predicted) and 10 physically active non-COPD (77±4 years old) older adults. The F-V relationship was evaluated in the leg press exercise during a purely concentric muscle action and compared with that following an eccentric muscle action at 10% intervals of maximal unloaded shortening velocity (V0). Vastus lateralis (VL) muscle thickness, pennation angle (PA) and fascicle length (FL) were assessed by ultrasound. Habitual gait speed was measured over a 4-m distance. COPD subjects exhibited lower physical function and concentric maximal muscle power (Pmax) values compared with the non-COPD group (both p<0.05). The SSC increased force and power values among COPD participants at 0-100% and 1-100% of V0, respectively, while the same was observed among non-COPD participants only at 40-90% and 30-90% of V0, respectively (all p<0.05). The SSC induced greater improvements in force, but not power, among COPD compared with non-COPD subjects between 50 and 70% of V0 (all p<0.05). Thus, between-group differences in muscle power were not statistically significant after the inclusion of the SSC (p>0.05). The SSC-induced potentiation at 50-100% of V0 was negatively associated with physical function (r = ‒0.40-0.50), while that observed at 80-100% of V0 was negatively associated with VL muscle thickness and PA (r = ‒0.43-0.52) (all p<0.05). In conclusion, older adults with COPD showed a higher SSC-induced potentiation compared with non-COPD subjects, which eliminated between-group differences in muscle power when performing SSC muscle actions. The SSC-induced potentiation was associated with lower physical function, VL muscle thickness and VL pennation angle values. The SSC-induced potentiation may help as a compensatory mechanism in those older subjects with a decreased ability to produce force/power during purely-concentric muscle actions.